Stakeholder Perceptions and The Role of Cultural Tourism in Achieving Sustainable Development at Osun Osogbo Sacred Grove, Nigeria - Osinubi, Olufemi Bankole; Ogunsusi, Kayode; Adeleke, Bola Olusola (Corpus Intellectual, 2025)
The Osun Osogbo Sacred Grove, a UNESCO World Heritage Site located in Osun State, Nigeria, represents a significant cultural and spiritual landmark in Yoruba land. As a major site for religious worship, traditional heritage, and cultural tourism, it plays a pivotal role in the sustainable socio- economic development of the region. This study investigated stakeholders’ perceptions and involvement in the cultural tourism potential and sustainable development of the Osun Osogbo Grove. Employing a descriptive survey research design, data were collected through structured questionnaires administered to 359 respondents drawn from four key stakeholder groups: religious adherents, vendors, tour service providers, and government officials. Statistical analyses including descriptive statistics, chi-square tests, and regression were applied to assess attitudinal dispositions and stakeholder contributions. Results revealed that while socio- demographic factors like age and education did not significantly influence attitudes toward cultural tourism, occupational type had a strong effect, suggesting the importance of stakeholder roles. Furthermore, stakeholder activities—particularly those of vendors, tour guides, cultural practitioners, and religious custodians—were found to significantly influence the development of cultural tourism attributes. Despite some challenges, such as conflicting stakeholder interests and the commercialization of cultural events, a majority of respondents confirmed the positive role stakeholders play in preserving cultural heritage and promoting sustainable tourism. The study concludes that stakeholder collaboration is essential for the sustained development of the Osun Osogbo Grove. It recommends enhanced policy support, stakeholder training, and inclusive planning frameworks to strengthen cultural tourism, preserve indigenous identity, and replicate this model in other heritage sites across Nigeria.